Perlidae (Plecoptera) from Bahia State, Brazil: description of the nymphs of Anacroneuria bahiensis Righi-Cavallaro & Lecci, notes on Anacroneuria debilis (Pictet), and updated list of the species - de Carvalho, Luana Ariel Cardoso; de Almeida, Lucas Henrique; Bispo, Pitágoras Da Conceição (Zootaxa, 2021)
In the present study, specimens of Anacroneuria (Plecoptera: Perlidae) from the Mucugê Municipal Park, Bahia State, Brazil were studied. The association between Anacroneuria bahiensis nymph and adult was possible because a specimen, as well as the exuviae, was collected during its emergence. Herein, we present the description of the A. bahiensis nymph, taxonomic notes on A. debilis, and an updated list of Anacroneuria species from Bahia State.